Efficient Sensor Interfaces, Advanced Amplifiers and Low Power RF Systems Advances in Analog Circuit Design 2015 - Makinwa, Kofi A.A.; Baschirotto, Andrea; Harpe, Pieter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is based on the 18 tutorials presented during the 24th workshop on Advances in Analog Circuit Design. Expert designers present readers with information about a variety of topics at the frontier of analog circuit design, including low-power and energy-efficient analog electronics, with specific contributions focusing on the design of efficient sensor interfaces and low-power RF systems. This book serves as a valuable reference to the state-of-the-art, for anyone involved in analog circuit research and development. ·         Provides a state-of-the-art reference in analog circuit design, written by experts from industry and academia; ·         Presents material in a tutorial-based format; ·         Includes coverage of high-performance analog-to-digital and digital to analog converters, integrated circuit design in scaled technologies, and time-domain signal processing.
Part 1.Efficient Sensor Interfaces -- Smart-DEM for Energy-Efficient Incremental ADCS -- Micro power Incremental Analog-to-Digital Converters -- Energy-Efficient CDCs for Millimeter Sensor Nodes -- A Micro-Power Temperature-to-Digital Converter for Use in a MEMS-Based 32kHz Oscillator -- Low-Power Biomedical Interfaces -- A Power-Efficient Compressive Sensing Platform for Cortical Implants -- Part 2. Advanced Amplifiers -- OpAmps, Gm-blocks or Inverters? -- Linearization Techniques for Push-Pull Amplifiers -- Ultra Low Power Low Voltage Capacitive Preamplifier for Audio Application -- Design and Technology for Very High-Voltage OpAmps -- Advances in Low-Offset OpAmps -- Amplifier Design for the Higgs Boson Search -- Part 3. Low-Power RF Systems -- PLL-Free, High Data Rate Capable Frequency Synthesizers -- Ultra Low Power Wireless SoC Design for Wearable BAN -- Towards Low Power N-Path Filters for Flexible RF-Channel Selection -- Efficiency Enhancement Techniques for RF and mm-Wave Power Amplifiers -- Energy-Efficient Phase-Domain RF Receivers for Internet-of-Things (IOT) Applications -- A Low-Power Versatile CMOS Transceiver for Automotive Applications.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation